Dashboard for the VISIR remote lab - Garcia-Zubia, Javier (2021)
The VISIR dashboard (VISIR-DB) is a learning analytics tool connected with the VISIR remote lab. In VISIR, every action performed by a student from the interface over the remote laboratory and back is logged and recorded. VISIR-DB helps visualizing, in a fast and deep way, the recorded logs from this communication. Using this tool, a teacher can analyze and understand better how the students are using the remote lab during their learning process on analog electronics. With this information, the VISIR platform can be improved and the use of remote labs can be better understood.